Pengaruh Variasi Pollen Terhadap Karakteristik Kimia Bee pollen - Ulfah Anis; Devi Silsia; Rizky Nirmala Kusumaningtyas (Jurnal Teknologi Agro-Industri, 2021)
Bee pollen contains high enough nutrition. Bee pollen contains some nutrients such as water, ash, lipid, protein, natural antioxidants, palmitic acid, oleic acid, linoleic acid, and linolenic acid. The high nutrients on bee pollen causes bee pollen to be widely used by many people as a food additive on some food productions. Bee pollen is widely used as a fortificant and substitute material. Bee pollen as a substitute material on the making of crackers. On snack bar making, bee pollen is used as a fortificant material. Bee pollen as a fortificant is also used on the making of milk to increase its nutrients, especially the polyphenols. One of the factors effecting the nutrient contents of bee pollen is the source of pollen. There are two sources of pollens, multiflora and uniflora. The aim of this experiment is to know the effect of pollen sources on water, ash, lipid, protein and crude fiber content in 3 types of commercial pollen in Indonesia. The result is bee pollen from 3 different plants pollen have a significant difference to proximate content including water, ash, lipid, protein, carbohydrate, and crude fiber. Keywords: bee pollen, proximate, pollen